Preliminary data on trace elements in tissues of Greenland shark Somniosus microcephalus from NE Greenland - ANCORA, STEFANIA; BIANCHI, NICOLA; MARIOTTI, GIACOMO; LEONZIO, CLAUDIO; CORSOLINI, SIMONETTA; Christiansen, Jörgen S. (country:ITA, 2012)
Somniosus microcephalus, Greenland shark, Greenland Sea, trace elements